National Relations : Public Diplomacy, National Identity and the Swedish Institute 1945-1970. - Glover, Nikolas (Nordic Academic Press, 2012)
In Stockholm in January of 1945, an assembly of Swedish diplomats and businessmen initiated an organization that was to improve the country's reputation abroad. The new, semi-governmental Swedish Institute was charged with explaining Sweden's policy of neutrality during the war, with encouraging peace-building, and with promoting foreign trade in the new international world order. Original and insightful, this account analyzes the policies, funding, and national narratives of the Swedish Institute. Providing a historical perspective on the politics of Swedish propaganda and explaining how idea.